THE MEDITATION INDUSTRY IN TERRENCE MALICK'S FILMS (World Bulletin of Social Sciences, 2022)
It talks about a distinct style in director Terrence Malick's films, about how meditation is made, as he is one of the directors affected by philosophical theories in Heidegger's philosophy on the other hand, and on the other hand, his interest in the religious and spiritual aspect, which resulted in the image he presents and its hidden presentation without him of the events and the characters that they present Therefore, his dealing with the image and sound can be unique because it depends on meditation as a basis in influencing the recipient and making it merging with what he is watching without using excitement, movement or suspense, and he is also concerned with the depth of the content image that montage and commenting techniques set from outside the staff and music to achieve it to move the insides of the recipient And his cognitive and psychological reserves in order to draw his attention to topics that may be familiar and circulating, but they were not present to him.